SEM studies on first and second gonopod morphology in Mithracidae (Decapoda: Brachyura) - Lianos, Laira [UNESP]; Mollemberg, Michelle [UNESP]; Zara, Fernando Jose [UNESP]; Tavares, Marcos; Santana, William [UNESP] (Soc Brasileira Carcinologia, 2021)
Gonopods are phylogenetically important morphological characters, and in several cases providing diagnostic characters to support taxonomic and phylogenetic studies. Relatively few studies, however, have emphasized indepth descriptions of gonopods, and the functional morphology of these structures are poorly understood. We use SEM to describe and illustrate the two pairs of gonopods (G1 and G2) of nine species of Mithracidae (Majoidea) and of Macrocoeloma trispinosum Latreille, 1825, recently relocated to Epialtidae (Majoidea). The G1 was found to present the typical characteristics of Majoidea: long, with a mesial suture, setae inserted from the base to the distal second third and sensilla in the apical plate; the G2 is always short and conical. The apical region of the G1 was diagnostic for the species analyzed, which could provide important characters for differentiating among the majoids; and also for studying the functional, reproductive, and phylogenetic significance of these structures.
Keywords: Majoidea; male reproductive system; scanning electron microscopy (SEM); taxonomy